Early outcomes of gastrostomy feeding in paediatric allogenic bone marrow transplantation: A retrospective cohort study. (June 2019) - Evans, James; Needle, Justin J.; Hirani, Shashivadan P.
Summary: Background: Nutrition support is an essential component of care for a child undergoing bone marrow transplantation (BMT). Enteral nutrition (EN) is becoming increasingly recognised as having advantages over parenteral nutrition (PN) and recommended as first-line nutrition support. EN has traditionally been provided via nasogastric tube (NGT). Gastrostomies avoid certain complications associated with NGTs and could provide a preferential alternative. Aims: To compare nutritional and post-transplantation outcomes during admission, the primary outcome being PN use, between children who had a gastrostomy placed prophylactically prior to BMT versus those who had not. Methods: Electronic medical records of children transplanted between January 2014 and May 2018 within a single-centre were retrospectively reviewed. Outcomes between the gastrostomy group (n = 54) and non-gastrostomy group (n = 91) were compared. Results: Multivariate regression analyses showed children in the gastrostomy group were less likely to require PN (odds ratio (OR) 0.4; 95% confidence interval (CI) 0.2–0.9; P  = 0.049), initiated PN later if required (hazard ratio 0.6; 95% CI 0.4–0.8; P  = 0.005), more often received EN as first-line nutrition support ( P  < 0.001) and more frequently required EN post-discharge (OR 2.4; 95% CI 1.1–5.4; P  = 0.029). No differences were found between groups on length of admission, day 100 overall survival, incidence of graft-versus-host-disease, positive blood cultures and changes in weight or albumin during admission. Conclusions: Providing EN via gastrostomy is feasible in this population and may be more acceptable to older children than NGTs. Weighing up the potential benefits against the potential risks of prophylactic gastrostomy placement in these high-risk children is a challenging decision. Further research investigating safety, longer-term outcomes and family perceptions of gastrostomy feeding is required.